Insight into proton transfer in phosphotungstic acid functionalized mesoporous silica-based proton exchange membrane fuel cells - Zhou, Yuhua (2014)
We have developed for fuel cells a novel proton exchange membrane (PEM) using inorganic phosphotungstic acid (HPW) as proton carrier and mesoporous silica as matrix (HPW-meso-silica) . The proton conductivity measured by electrochemical impedance spectroscopy is 0.11 S cm–1 at 90 °C and 100% relative humidity (RH) with a low activation energy of 14 kJ mol–1. In order to determine the energetics associated with proton migration within the HPW-meso-silica PEM and to determine the mechanism of proton hopping, we report density functional theory (DFT) calculations using the generalized gradient approximation (GGA). These DFT calculations revealed that the proton transfer process involves both intramolecular and intermolecular proton transfer pathways. When the adjacent HPWs are close (less than 17.0 Å apart), the calculated activation energy for intramolecular proton transfer within a HPW molecule is higher (29.1–18.8 kJ/mol) than the barrier for intermolecular proton transfer along the hydrogen bond. We find that the overall barrier for proton movement within the HPW-meso-silica membranes is determined by the intramolecular proton transfer pathway, which explains why the proton conductivity remains unchanged when the weight percentage of HPW on meso-silica is above 67 wt %. In contrast, the activation energy of proton transfer on a clean SiO2 (111) surface is computed to be as high as 40 kJ mol–1, confirming the very low proton conductivity on clean silica surfaces observed experimentally.